Analisis Semiotika Roland Barthes Pesan Dakwah Habib Husein Ja’far Al Hadar Dalam Youtube Has Creative - Aditya, Ibnu; Deni, Indira Fatra (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
His contemporary and easy-to-digest da'wah content, Habib Husein Jafar Al Hadar has become a social media star. This research aims to understand the meaning of da'wah messages and classify da'wah messages based on creed, sharia, and morals using social media such as Youtube. This research uses Roland Barthes' semiotic theory and descriptive qualitative methodology to obtain data through observation and recording. Based on myth, meaning, and denotation, Habib Ja'far's da'wah emphasizes tawakal, patience, meditation, and social duty. We interpret the concepts of Islam in this course. In this episode, the misconceptions of Muslims are explained. podcast that emphasizes sharia, morals, and aqidah.